2019
DOI: 10.12691/ajnr-7-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Quality of Life and Work Productivity among Patients with Gout

Abstract: Gout is the most common inflammatory arthritis today, affecting 4% of the adult US population. It is a serious disease that can significantly affect physical function and quality of life (QOL), where it has been advocated as an important outcome domain in studies of chronic gout. Aim of the study: To assess factors affecting quality of life and work productivity among patients with gout. Descriptive design: Was used to conduct the current study in rheumatology outpatient clinics, at Benha Teaching Hospital dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Participants completed the following standardized, validated questionnaires and instruments: Short Form-36 version 2 (SF36v2) ( 40 , 41 ) questionnaire, the World Endometriosis Research Foundation EPHect (WERF-EPHect) minimum clinical questionnaire (EPQ-M) version ( 42 ), and Work Productivity and Activity Impairment (WPAI) ( 43 , 44 ) questionnaire. Translations to the Arabic language, validated using the forward-backward translation method, of the questionnaires were utilized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants completed the following standardized, validated questionnaires and instruments: Short Form-36 version 2 (SF36v2) ( 40 , 41 ) questionnaire, the World Endometriosis Research Foundation EPHect (WERF-EPHect) minimum clinical questionnaire (EPQ-M) version ( 42 ), and Work Productivity and Activity Impairment (WPAI) ( 43 , 44 ) questionnaire. Translations to the Arabic language, validated using the forward-backward translation method, of the questionnaires were utilized.…”
Section: Methodsmentioning
confidence: 99%
“…WERF-EPHect questionnaire (EPQ-M) were used to collect demographic information, measure the presence and severity of symptoms, risk factors, phenotypic profile and physical activity assessment ( 42 , 45 ). WPAI was used to measure absenteeism and presenteeism in employed women, and the impact of symptoms on activities ( 43 , 44 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any conditions that lead to the excessive accumulation of uric acid inside the body, for instance, low excretion and/or over-production will cause hyperuricemia, which in turn, could lead to a type of painful inflammatory arthropathy commonly known as gout [4,5]. The prevalence of gout varies across the world [6] and is estimated to occur in approximately 4.75% of European countries [6], 4% for USA [7], and >1% for Asia [6,8] and Africa [6]. It has been shown that gout patients had higher risk for developing cancer, particularly cancer of the lungs, urological and digestive systems [9].…”
Section: Introductionmentioning
confidence: 99%